Small-sample tests for stock return predictability with possibly non-stationary regressors and GARCH-type effects - Sermin Gungor; Richard Luger (Bank of Canada, 2017)
We develop a simulation-based procedure to test for stock return predictability with multiple regressors. The process governing the regressors is left completely free and the test procedure remains valid in small samples even in the presence of non-normalities and GARCH-type effects in the stock returns. The usefulness of the new procedure is demonstrated both in a simulation study and by examining the ability of a group of financial variables to predict excess stock returns. We find robust evidence of predictability during the period 1948-2014, driven entirely by the term spread. This empirical evidence, however, is much weaker over subsamples.
Keywords: C12; C32; G14; 330; Econometric and statistical methods; Asset pricing; Financial markets